Effectiveness of Game-Based Learning – Learning in Modern Education - Wardoyo, Cipto; Dwi Satrio, Yogi; Ma’ruf, Dudung (KnE Social Sciences, 2020)
The experiential learning process is a relevant method used to enhance understanding of the field and the critical thinking skills of learners. Futher more, technological developments improve students ’ learning needs. In this case, learners are required to be able to learn and work dynamically by combining the concept of critical thinking and the way of life as demand for the 21st century. Therefore, dynamic learning and the ability to improve the cognitive and collaborative abilities of learners in their interactions with the environment and all changes are indispensable. This research aims to spread the educational game quiz Assistance to create fun and dynamic learning for students. In addition, developed media is expected to improve cognitive ability and critical thinking learners, especially in higher education. The development of this educational game is done in the economic field so that the material to be presented is a basic course of economics faculty. To measure the success of this game-based learning, researchers used 100 samples from three majors (development economics, management, and accounting). This method of analysis uses the method of gain-scores, where the learning outcomes of experimental Group with learning game treatment and control group learning outcomes are examined and analyzed to determine their effectiveness. Results from analyses showed that use of game- based learning is highly effective for improving learning outcomes. Keywords: Technology, educational game, game based learning, gamification Learning.